Antifungal activity of volatile organic compounds produced by Pseudomonas fluorescens ZX and potential biocontrol of blue mold decay on postharvest citrus. (February 2021) - Wang, Zhirong; Zhong, Tao; Chen, Kewei; Du, Muying; Chen, Guangjing; Chen, Xuhui; Wang, Kaituo; Zalán, Zsolt; Takács, Krisztina; Kan, Jianquan
Abstract: In this research, postharvest citrus fruits with blue mold caused by Penicillium italicum were treated with volatile organic compounds (VOCs) produced by Pseudomonas fluorescens ZX incubated on NA and in NB. Treatments with pure individual components of the VOCs were also conducted. The VOCs from P. fluorescens ZX inhibited mycelial growth and conidial germination of P. italicum by 42.14% and 77.86%, respectively. In vivo experiments revealed that blue mold disease incidence and lesion size upon fruits were significantly suppresed by VOCs from P. fluorescens ZX incubated on NA, in NB and on healthy fruits. In addition, the VOCs produced by bacterial fluid provided higher biocontrol efficacy than did that from NA plates. The exposure to VOCs from bacterial fluid of P. fluorescens ZX resulted in morphological abnormalities of the conidia and hyphae of P. italicum . In vitro testing of the individual pure compounds comprising the VOCs suggested that organic acids and sulfur compounds are the active components of VOCs, with dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) exhibiting the highest antifungal activity: concentrations of only 100 and 10 μL/L, respectively, afforded complete inhibition of blue mold on citrus fruits in vivo. Organic acids showed promise for controlling blue mold, but only in sufficiently low concentrations so as not to promote physiological disease or damage in the fruits. Highlights: Production of VOCs is an important biocontrol mechanisms of P. fluorescens ZX. Culture conditions have effects on types and antifungal activity of VOCs from BCAs. SMOAs are promising for controlling blue mold on citrus fruits at appropriate dose. DMDS and DMTS show the highest inhibitory effects among all VOCs.